The effectiveness of using situational awareness and case-based seminars in a comprehensive nursing skill practice course for undergraduate nursing students: a quasi-experimental study - Yuanhao Sun; Xiangdong Li; Haiyang Liu; Yuqing Li; Jiaofeng Gui; Xiaoyun Zhang; Xiaoping Li; Lu Sun; Lin Zhang; Congzhi Wang; Jing Li; Mingming Liu; et al. (BMC Medical Education, 2024)
Abstract Background Nurses play an important role in healthcare development. The increasing demands for nurses mean that nursing schools at the undergraduate level have the responsibility to ensure patient safety and quality care through a well-designed curriculum. This research aimed to evaluate the effect of the teaching method combined with situational awareness and case-based seminars in a comprehensive nursing skills practice course on the level of self-directed learning, professional identity, academic self-efficacy, theoretical scores, practical scores, teaching satisfaction, and student competence among nursing students. Methods The research population comprised was of the grades of 2019 and 2020 at Wannan Medical College in Anhui Province, China (n = 169, response rate 77.88%). The observation group from grade 2020 used the teaching method combined with situational awareness and case-based seminars, whereas the control group from grade 2019 used the traditional teaching mode. General information, self-directed learning, a professional identity, and academic self-efficacy were compared between the two groups. This research used means and standard deviations, chi-square, the Shapiro–Wilk test, and an independent sample t-test for statistical analyses. Results Compared with the control group, the total scores for self-directed learning, professional identity, and academic self-efficacy were higher in the observation group (78.80 ± 7.89 vs 60.21 ± 7.44, 63.39 ± 7.87 vs 52.35 ± 7.68, and 22.31 ± 3.30 vs 21.28 ± 2.31, respectively, with P < 0.05 for all scores). More significant improvements were made in the observation group on the level of theoretical scores (81.39 ± 3.32 vs 76.28 ± 5.90) and practical scores (93.32 ± 4.70 vs 90.67 ± 5.09) (P < 0.05). Meanwhile, teaching satisfaction, which includes teaching method (66/18 vs 32/53) and teacher-student interaction (72/12 vs 34/51), and student competence, which includes team cooperation (67/17 vs 39/46), critical thinking (60/24 vs 31/54), and communication skills (67/17 vs 38/47) after the intervention (P < 0.05). There was no significant difference in social persuasion (P > 0.05). Conclusion The teaching method combined with situational awareness and case-based seminars in a comprehensive nursing skills practice course has the potential to improve the level of self-directed learning, professional identity, and academic self-efficacy, and it increases theoretical scores, practical scores, teaching satisfaction, and student competence.